Prediction of paclitaxel resistance in breast cancer: is CYP1B1*3 a new factor of influence?. (July 2008) - Gehrmann, Mathias; Schmidt, Markus; Brase, Jan C; Roos, Peter; Hengstler, Jan G
This article focuses on the recent findings by Marsh and colleagues, and also discusses recent findings with regards to breast cancer. Taxanes are amongst the most active agents in the treatment of breast cancer. However, many tumors are intrinsically resistant. Therefore, it would be an enormous progress, if factors could be identified that reliably differentiate between taxane-sensitive and -resistant patients. Marsh and colleagues analyzed the CYP1B1*3 (Val432Leu) polymorphism in patients with high-risk stage III and IV breast cancer, who received dose-intense paclitaxel in combination with doxorubicin and cyclophosphamide. They report for the first time that patients with two leucine alleles in codon 432 of CYP1B1 experience a longer progression-free survival compared with patients with the Val/Leu or Val/Val genotypes. If confirmed in independent cohorts CYP1B1*3 may prove to be an important factor that helps to differentiate between paclitaxel-sensitive and resistant breast cancer patients. However, the mechanism behind the association between CYP1B1*3 and prognosis of paclitaxel-treated patients remains unclear. Several studies provide strong evidence that CYP1B1 does not influence tumor progression independently from paclitaxel chemotherapy, and that CYP1B1 itself does not alter paclitaxel resistance. In addition, CYP1B1 mRNA expression does not correlate with paclitaxel sensitivity of primary tumor cells. Although still speculative, a possible explanation is an association between CYP1B1*3 with still unknown factors that, on their part, influence paclitaxel sensitivity. In the future, studies with SNP chips and studies on the transcriptome, proteome and metabolome level should be performed in order to identify signatures differentiating between paclitaxel-sensitive and -resistant patients.